2019
DOI: 10.1097/brs.0000000000003148
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes at Skeletal Maturity of 34 Children With Scoliosis Treated With a Traditional Single Growing Rod

Abstract: Study Design. Retrospective case series. Objectives. To analyze the outcomes at skeletal maturity of patients treated with a single traditional growing rod (GR). To compare results of patients according to whether posterior spinal fusion (PSF) was performed at treatment completion. Summary of Background Data. Few studies examined the end results of GRs at skeletal maturity. There is no agreement on requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…In our previous study, the growing rod treatment of early-onset scoliosis, in which main thoracic scoliosis and thoracic kyphosis were signi cantly improved at the last follow-up indicators compared with preoperative 18 .Single growing rods can effectively improve the angle of scoliosis and maintain spinal growth, although they are not equivalent with the dual rods in preventing internal xation breakage and maintaining the corrective angle. 19 In our study,30 patients (83.3%) were treated with a single rod, and 6 patients (26.1%) were treated with a dual rod(P < 0.05).Dual rod surgery has been mainly completed recently because the foundation has funded the treatment of children in high-altitude areas, with a total of 12 patients in the H-A group and 18 in the L-A group who underwent subcutaneous growing rod implantation, while the other patients were implanted growing rods submuscularly(P = 0.871).A meta-analysis of single and dual rod treatment of EOS have showed that dual growing rod implantation can achieve better deformity correction and spinal growth. The incidence of complications related to internal xation is low, while the dual rod group internal xation has a high complication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, the growing rod treatment of early-onset scoliosis, in which main thoracic scoliosis and thoracic kyphosis were signi cantly improved at the last follow-up indicators compared with preoperative 18 .Single growing rods can effectively improve the angle of scoliosis and maintain spinal growth, although they are not equivalent with the dual rods in preventing internal xation breakage and maintaining the corrective angle. 19 In our study,30 patients (83.3%) were treated with a single rod, and 6 patients (26.1%) were treated with a dual rod(P < 0.05).Dual rod surgery has been mainly completed recently because the foundation has funded the treatment of children in high-altitude areas, with a total of 12 patients in the H-A group and 18 in the L-A group who underwent subcutaneous growing rod implantation, while the other patients were implanted growing rods submuscularly(P = 0.871).A meta-analysis of single and dual rod treatment of EOS have showed that dual growing rod implantation can achieve better deformity correction and spinal growth. The incidence of complications related to internal xation is low, while the dual rod group internal xation has a high complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dual growing rods can be retained instead of performing nal fusion surgery. 19 In our study, the overall incidence of complications in the H-A and L-A groups was 60.9% and 63.9%, respectively, and the difference was not statistically signi cant(P = 0.815).The incidence of implant-related complications in the L-A group(63.9%) was higher than that in the H-A group(52.2%), but the difference was not statistically signi cant (P = 0.372).Most children with EOS in the H-A group have been subsidized through spinal rescue action recently, and the progress of the treatment concept, the improvement of surgical techniques, and the improvement of internal xation equipment all promote further reduction of implant-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…19 Single growing rods can effectively improve the angle of scoliosis and maintain spinal growth,although they are not equivalent with the dual rods in preventing internal xation breakage and maintaining the corrective angle. 20 Here,30 patients (83.3%) were treated with a single rod, and 6 patients (26.1%) were treated with a dual rod(P < 0.05).Dual rod surgery has been mainly completed recently because the foundation has funded the treatment of children in high-altitude areas, with a total of 12 patients in the H-A group and 18 in the L-A group who underwent subcutaneous growing rod implantation, while the other patients were implanted with growing rods submuscularly(P = 0.871).A meta-analysis of single and dual rod treatment of EOS has showed that dual growing rod implantation can achieve better deformity correction and spinal growth. The incidence of complications related to internal xation was lower in the in the single rod group than in the dual rod group.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,17 The incidence of internal xation-related complications was 54.2%,and the incidence of surgical site infection was 22.7%. 18 Bouthors 20 retrospectively analyzed 34 patients with single growing rods for EOS.Although single growing rods can achieve good results in deformity correction and maintenance of spinal growth, the IRCs are especially high. Hence, it is recommended that dual growing rods be used for patients over 8 years old as such rods can better prevent breakage and maintain the orthopedic effect for patients with satisfactory orthopedics after bone maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed a progressive and delayed stiffening of the spine in the oldest cases, induced by the presence of metallic rods implanted several years ago. 14,15 Finally, performing this technique early on, in an immature child, provides undeniable comfort to the patient as well as dispensing with the need for a brace. It reduces the overall cost of treatment for the public health service, thanks to the reduced number of implants, the low rate of complications and shorter hospital stays, especially in the ICU, when compared to the traditional techniques.…”
Section: Discussionmentioning
confidence: 99%